Computer Chess Compendium (Springer-Verlag, 2020)
The remarkable increase in strength of chess computers over the last ten years has resulted in a flood of books and articles on programming methods and new approaches to analysing positions. All important articles on the subject have now been collected together in one volume together with the best games by chess computers including the World Computer Championships. Every article has been transliterated into algebraic notation and an extensive bibliography provides scope for further research. This book will appeal to all chess players and computer enthusiasts, particularly those interested in artificial intelligence. David Levy is one of the world's leading authorities on computer chess and is author of Chess and Computers, More Chess and Computers and the Chess Computer Handbook